Rhonni D. answered • 09/16/16

Tutor

4.8
(22)
Grade A Math & Computer Tutor

Set up the equations as s (sandwiches); h (hotdogs):

3s + h = 65

s + 3h = 35

Use the elimination of 1 variable to solve for the other.

Eliminating h and solving for s:

3s + h = 65

s + 3h = 35 (multiply this by -3)

s + 3h = 35 (multiply this by -3)

-------------------------------------

3s + h = 65

-3s - 9h = -105

-3s - 9h = -105

------------------

-8h = -40

h = 5 (hotdogs cost $5 each)

Now, substitute h in 1 of the equations to solve for s:

3s + 5 = 65

-5 -5

---------------

3s = 60

s = 20 (sandwiches cost $20 each)

Check the 2 equations:

3(20) + 5 ? 65

60 + 5 ? 65

65 = 65 (check)

20 + 3(5) ? 35

20 + 15 ? 35

35 = 35 (check)

Now, solve for the last one:

2s + 2h = ?

2(20) + 2(5) = ?

40 + 10 = 50 (the cost for 2 hotdogs and 2 sandwiches)